The creatine kinase pathway is a metabolic vulnerability in EVI1-positive acute myeloid leukemia - Fenouille, Nina; Bassil, Christopher F; Ben-Sahra, Issam; Benajiba, Lina; Alexe, Gabriela; Ramos, Azucena; Pikman, Yana; Conway, Amy S; Burgess, Michael R; Li, Qing; Luciano, Frédéric; Auberger, Patrick; et al. (Nature medicine, 2017)
Transcriptomic and metabolic profiling reveals that the creatine kinase pathway is essential for growth of acute myeloid leukemias expressing the transcription factor EVI1. Expression of the MECOM (also known as EVI1 ) proto-oncogene is deregulated by chromosomal translocations in some cases of acute myeloid leukemia (AML) and is associated with poor clinical outcome. Here, through transcriptomic and metabolomic profiling of hematopoietic cells, we reveal that EVI1 overexpression alters cellular metabolism. A screen using pooled short hairpin RNAs (shRNAs) identified the ATP-buffering, mitochondrial creatine kinase CKMT1 as necessary for survival of EVI1-expressing cells in subjects with EVI1-positive AML. EVI1 promotes CKMT1 expression by repressing the myeloid differentiation regulator RUNX1. Suppression of arginine–creatine metabolism by CKMT1 -directed shRNAs or by the small molecule cyclocreatine selectively decreased the viability, promoted the cell cycle arrest and apoptosis of human EVI1-positive cell lines, and prolonged survival in both orthotopic xenograft models and mouse models of primary AML. CKMT1 inhibition altered mitochondrial respiration and ATP production, an effect that was abrogated by phosphocreatine-mediated reactivation of the arginine–creatine pathway. Targeting CKMT1 is thus a promising therapeutic strategy for this EVI1-driven AML subtype that is highly resistant to current treatment regimens.